Effect of perceived stress, job satisfaction, and workload on the professional self-efficacy of Peruvian regular basic education teachers - Belizario, Marleni Velez; Mamani-Benito, Oscar; Zerga-Morales, Carlos Alejandro; Turpo-Chaparro, Josué E.; Morales-García, Wilter C. (Frontiers in Education, 2024)
The COVID-19 pandemic has had repercussions on teachers' beliefs about their efficacy in their profession. In light of this, the aim of this study was to determine the effect of perceived stress, job satisfaction, and workload on professional self-efficacy among Peruvian regular basic education teachers.Method: This was a cross-sectional explanatory study involving 687 regular basic education teachers (57.6% women) aged between 23 to 55 years (M=38.15, SD=8.58), from both private and public institutions across the three regions of Peru (coastal, jungle and highland). The instruments used were the Professional Self-Efficacy Questionnaire (AU-10), the Perceived Stress Scale related to the pandemic (EEP-10), the Affective Job Satisfaction Scale (BIAJS), and the Workload Scale (ECT).Results: A SEM analysis was conducted, yielding satisfactory goodness-of-fit indices: χ 2 = 87.028, p = .000, with 11 df, CFI = .993, RMSEA = .047, and SRMR = .021. This confirmed H1, as there is a negative effect of workload on professional self-efficacy (β = -.11, p = .017). Similarly, H2 was confirmed, as there is a positive effect of job satisfaction on professional self-efficacy (β = .13, p = .003). However, H3 was rejected, as no significant effect of perceived stress on professional selfefficacy was evident (β = -.02, p = .658). Conclusions: Workload and job satisfaction explain the perceived level of self-efficacy among Peruvian regular basic education teachers. However, there is no evidence to suggest that stress affects their sense of efficacy.